The most common etiological factors of conjunctivitis - Ewa Jasińska; Katarzyna Adamczyk; Rafal Wojcik; Dorota Adamczyk; Katarzyna Nowomiejska; Alina Olender (Kazimierz Wielki University, 2018)
Conjunctivitis is one of the most common diseases of the anterior segment. It is characterized by redness of the eye, conjunctivital injection, the presence of secretions in the conjunctival sac. The most common symptoms reported by patients include: pain, redness, itching, foreign body sensation and photophobia. Intensifying severe symptoms can lead to difficulties in daily activities. The correct diagnosis of the etiological agent is essential to implement an appropriate treatment and relieve symptoms of the disease.